Environmental-based diseases of students in urban and rural areas, Lampung province, Indonesia - Saidi, Subian; Herawati, Netti; Nisa, Khoirin (International Journal of Innovative Research and Scientific Studies, 2023)
The aim of this study is to examine environmental-based diseases among students in Lampung Province, Indonesia. A total of 1,000 students from all districts in Lampung Province participated. Subsequently, the student disease distribution was grouped using the ROCK (Robust Clustering Using LinKs) method. The results indicated that many students were in a cluster often exposed to environmental-based diseases (cluster 4). The type of environmental-based disease that mostly affects the students in cluster 4 is skin disease while very few suffer from intestinal worms. The results of this study also demonstrated that students in rural areas suffer more from environmental-based diseases than those who live in urban areas. The majority of students in urban areas suffered from air-sensitive diseases (42%). Cluster 4 was the group of students who suffered from environmental-based diseases. Environmental-based diseases arise or recur due to environmental pollution such as acute respiratory infections (ARIs), diarrhea, intestinal worms, pulmonary tuberculosis and skin diseases. This may be due to the lack of awareness and knowledge of students in rural areas regarding the importance of protecting the environment in order to avoid environmental-based diseases.